Primary School Pupils’ Performance on the Addition of Fractions: Conceptual and Procedural Knowledge - Abbas, Nor’ Arifahwati; Abdullah, Nor Azura; Shahrill, Masitah; Tengah, Khairul Amilin (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
Fractions remain predominantly one of the most challenging topics to teach and learn. Brunei Darussalam is no exception, where a few local researches reported that students performed poorly in fraction topics. To understand this situation, this study focuses on pupils’ understanding in solving problems on fractions. Specifically, this study investigated Year 5 pupils’ conceptual and procedural performance on the addition of fractions. This study employed a quantitative research approach involving 572 primary school children. A test consisting of six carefully planned questions on fractions was used as the research instrument. The questions were divided into two sections to test pupils’ conceptual and procedural understanding laterally. The findings from this study revealed that children performed better in the procedural than in the conceptual questions. It can be concluded that most Year 5 pupils can correctly attempt the addition of fractions via procedural approach without understanding the essential concepts involved. Recommendation for future research was also discussed.DOI : https://doi.org/10.22342/jpm.16.2.17811.227-238